Development of expanded host range phage active on biofilms of multi-drug resistant Pseudomonas aeruginosa. Issue 1 (2nd January 2016) - Mapes, Abigail C.; Trautner, Barbara W.; Liao, Kershena S.; Ramig, Robert F.
ABSTRACT: Phage therapy is a promising treatment of multi-drug resistant (MDR) bacterial infections but is limited by the narrow host range of phage. To overcome this limitation, we developed a host range expansion (HRE) protocol that expands the host range of Pseudomonas aeruginosa -specific phage by cycles of co-incubation of phage with multiple P. aeruginosa strains. Application of the HRE protocol to a mixture of 4 phages, using 16 P. aeruginosa strains for development, resulted in undefined phage mixtures with greatly expanded host range. Individual phage clones derived from the undefined mixture had expanded host ranges but no individual clone could lyse all of the strains covered by the undefined mixture from which it was isolated. Reconstituting host range-characterized clones into cocktails produced defined cocktails with predictable and broad host ranges. The undefined mixture from the 30 th cycle of the mixed-phage HRE (4φC 30 ) showed a dose-dependent ability to prevent biofilm formation by, and to reduce a pre-existing biofilm of, 3 P. aeruginosa clinical isolates that produced high amounts of biofilm. A defined cocktail reconstituted from 3 host range-characterized clones had activity on high biofilm-formers susceptible to the phage. Phage therapy was superior to antibiotic therapy (levofloxacin) in a strain of P. aeruginosa that was resistant to levofloxacin. The HRE protocol establishes a rapid approach to create libraries of phage clones and phage cocktails with broad host range, defined composition and anti-biofilm activity.